Evaluation of models to generate connectivity routes between protected natural areas in Granma, Cuba - Rodríguez Cueto, Yandy (2022)
[Introduction]: Most of the research dealing with connectivity route use cost-distance maps generated from the creation of ranges of the variables employed. [Objective]: This research evaluates the effect of the selected method for cost-distance map computation over the network of connectivity routes among viable vegetation patches in the protected areas of Granma province, Cuba. [Methodology]: The process generates two cost-distance raster (one with ranges and one without ranges) from which the connectivity routes are obtained. Additionally, the research includes the analysis of the effect of the selected method for raster computation over the connectivity route network. [Results]: The method identifies 3 080 routes. Route density for raster with ranges reaches 1 000 route/km2, while route density for raster without ranges reaches 3 000 route/km2. The 59 % of the routes for the raster with ranges is altitudinal, while the 75.8 % of the routes for the raster without ranges is altitudinal. [Conclusions]: The modification in the computation of the cost raster to displacement generates changes in the route network and concentration of the routes at the sites of connection between zones in the study area. Additionally, the values of route density change depending on the method of the cost raster computation, as well as the altitudinal condition of the routes.